2018
DOI: 10.1007/s12311-018-0971-0
|View full text |Cite
|
Sign up to set email alerts
|

Both 50 and 30 Hz continuous theta burst transcranial magnetic stimulation depresses the cerebellum

Abstract: The cerebellum is implicated in the pathophysiology of numerous movement disorders, which makes it an attractive target for noninvasive neurostimulation. Continuous theta burst stimulation (cTBS) can induce long lasting plastic changes in human brain; however, the efficacy of different simulation protocols has not been investigated at the cerebellum. Here, we compare a traditional 50-Hz and a modified 30-Hz cTBS protocols at modulating cerebellar activity in healthy subjects. Seventeen healthy adults participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Therefore, cerebellar brain inhibition (CBI) refers to an inhibition of the motor cortex due to activation of Purkinje cells ( Ugawa et al, 1995 ; Daskalakis et al, 2004 ). It has been observed that cerebellar stimulation can modulate CBI by altering the activity of Purkinje cells, resulting in continuous and polarity-related bidirectional regulation of cerebellar excitability ( Koch, 2010 ; Strzalkowski et al, 2019 ). Cerebellar iTBS could indirectly regulate the dentate nucleus by activating local low-threshold interneurons.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, cerebellar brain inhibition (CBI) refers to an inhibition of the motor cortex due to activation of Purkinje cells ( Ugawa et al, 1995 ; Daskalakis et al, 2004 ). It has been observed that cerebellar stimulation can modulate CBI by altering the activity of Purkinje cells, resulting in continuous and polarity-related bidirectional regulation of cerebellar excitability ( Koch, 2010 ; Strzalkowski et al, 2019 ). Cerebellar iTBS could indirectly regulate the dentate nucleus by activating local low-threshold interneurons.…”
Section: Discussionmentioning
confidence: 99%
“…However, if the interactions between the cerebellum and the basal ganglia thalamocortical circuits are of any significance in movement disorders, it may be most effective to concentrate on the goal of stimulating cerebellar efferents that either directly or indirectly influence basal ganglia function. While the benefits resulting from chronic stimulation of the cerebellar cortex were significant [67, 131, 297306], it may be easiest to focus invasive stimulation approaches (such as DBS) on the deep cerebellar nuclei (or on the pathways emanating from them), given the substantial topographic spread of motor representations along the cerebellar cortex. To optimize this approach, a good understanding of the functional connectivity of specific deep cerebellar nuclei would be needed.…”
Section: Mechanism(s) Of Cerebellar Stimulationmentioning
confidence: 99%
“…The method of cerebellar stimulation may explain some of the discrepancies in the literature. For instance, while electrical stimulation of the cerebellar cortex may have activated Purkinje cell output to the deep cerebellar nuclei (and may, thus, have had produced inhibitory effects in brain areas receiving cerebellar output), recent studies have suggested that at least some forms of TMS of the cerebellum (e.g., continuous theta-burst stimulation) lead to reduced cerebellar activity ([306]; see section by Popa and Hallett).…”
Section: Mechanism(s) Of Cerebellar Stimulationmentioning
confidence: 99%
“…www.nature.com/scientificreports/ studies [56][57][58][59] , since five probands in a pilot study did not tolerate the stimulation due to pain and discomfort, and a figure-of-eight-shaped coil was frequently used in previous CBI studies 18,20,23,54,[60][61][62] . MEPs were generated by a supra-threshold intensity of 120% RMT and evoked an MEP of about 1 mV.…”
Section: Transcranial Magnetic Stimulation Single-and Multi-pulse Tmmentioning
confidence: 99%